Knowledge, attitues, and practices of clinicians from dental schools in the city of Manila on the use of protective eyewear - Co, Carmina Jocel T.; Majan, Ezekiel S.; Remulla, Maxine Anne A.; Sia, Paul Benzo I. (Department of Community Dentistry, University of the Philippines Manila, 2018)
Introduction: Dental health care practitioners and their patients are exposed to pathogens and hazards during dental procedures. This warrants stringent protocols on the use of personal protective equipment including protective eyewear. This study is focused on determining the knowledge, attitudes, and practices of clinicians from dental schools in the City of Manila, as well as identify the existing policies of the selected schools regarding the use of protective eyewear.